Tadabbur Fiṭra as a Spiritual Coping Strategy for Parents of Children with Cancer at YKAKI of Central Java - Fitriyati Fitriyati; Tsuwaibah Tsuwaibah; Suripto Suripto (Teosofia: Indonesian Journal of Islamic Mysticism, 2025)
Parents of children with cancer face various problems, including emotional, spiritual, and practical challenges that often require them to develop resilient coping behaviours. This article examines how the internalization of tadabbur fiṭra affects and helps parents' coping strategies at YKAKI (Yayasan Kasih Anak Kanker Indonesia). Using a qualitative approach, including in-depth interviews and participant observation, this study found that internalizing tadabbur fiṭra helps parents reconnect with their innate trust in God (tawakkal), gratitude (shukr), and acceptance (riḍā), thereby fostering deeper spiritual strength and emotional stability. These findings highlight the transformative potential of integrating spiritual practices into psychosocial interventions for parents in similar contexts. Coping behaviours based on internalizing tadabbur fiṭra can enhance parents' well-being and their capacity to support their children during health crises.Contribution: This study contributes to the intersection of spirituality, health psychology, and family resilience, offering practical implications for spirituality-based healthcare programs.